Pengaruh Profesionalisme dan Kompetensi Pengawas Internal Pemerintah APIP Terhadap Kualitas Audit (Studi pada Inspektorat Kabupaten Serang) - Eli Apud Saepudin; Fithrotul Kamilah; Rizki Amilia; Putri Handayani (UNIVERSITAS SERAMBI MEKKAH, 2024)
This study aims to examine the influence of professionalism and competence of internal control on audit quality (Case Study of the Inspectorate of Banten Province). This study develops a theoretical framework as a basic hypothesis, to answer research questions which consist of how professionalism influences audit quality, and how competence influences audit quality. The sample for this study was 83 Government Internal Audit Apparatuses (APIP) at the Inspectorate of Banten Province. This study uses the census method. The data used is primary data collected through questionnaires. The data analysis method for testing the hypothesis is Structural Equation Modeling (SEM) analysis using Partial Least Square (PLS). The results of this study indicate that: (1) professionalism has a positive and significant effect on audit quality, and (2) competence has a positive and significant effect on audit quality.